The definition and measurement of electromagnetic chirality. (26th October 2017) - Arens, Tilo; Hagemann, Felix; Hettlich, Frank; Kirsch, Andreas
Abstract : The notion of electromagnetic chirality, recently introduced in the Physics literature, is investigated in the framework of scattering of time‐harmonic electromagnetic waves by bounded scatterers. This type of chirality is defined as a property of the farfield operator. The relation of this novel notion of chirality to that of geometric chirality of the scatterer is explored. It is shown for several examples of scattering problems that geometric achirality implies electromagnetic achirality. On the other hand, a chiral material law, as for example given by the Drude‐Born‐Fedorov model, yields an electromagnetically chiral scatterer. Electromagnetic chirality also allows the definition of a measure. Scatterers invisible to fields of one helicity turn out to be maximally chiral with respect to this measure. For a certain class of electromagnetically chiral scatterers, we provide numerical calculations of the measure of chirality through solutions of scattering problems computed by a boundary element method.